Liver metastasis from hepatoid adenocarcinoma of the stomach: a case report and literature review - Zhu, Hui; Li, Qingqing; Qian, Linqing (Frontiers in Oncology, 2024)
Hepatoid adenocarcinoma of the stomach (HAS) represents a rare malignant neoplasm sharing morphological and immunophenotypic similarities with hepatocellular carcinoma (HCC). Pathological morphology serves as the cornerstone for diagnosis, often accompanied by elevated alpha-fetoprotein (AFP) levels, nonspecific clinical symptoms, and imaging features reminiscent of gastric adenocarcinoma (GA). Liver metastases from HAS can mimic the enhancement patterns of HCC, posing challenges in differentiation from high-risk HCC cases. Conversely, HAS typically exhibits poorer prognostic outcomes compared to HCC and GA. This report presents a case of HAS with liver metastasis alongside a comprehensive literature review covering its pathology, molecular mechanisms, clinical presentations, and treatment modalities. Special focus is given to imaging characteristics and the utilization of radiomics for early-stage detection. The integration of imaging findings with laboratory results aids in HAS diagnosis, while radiomics provides novel insights for precise discrimination. In conclusion, the identification of distinct imaging markers distinguishing HAS from HCC and GA shows promise in facilitating optimal treatment strategies and improving patient outcomes.